PENGARUH PEMBELAJARAN DARI RUMAH TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK - Reka Tia Susanti; Waspodo Waspodo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to determine and analyze the effect of learning from home on learning motivation and to know and analyze the effect of learning from home on learning outcomes at SMK Negeri 2 Kayuagung. In this study using primary data and secondary data, primary data were obtained by distributing questionnaires to 46 students as sample respondents. The quatitative reseach is used. Simple resression was used to analyse the data by using SPSS 22 version in model development and hypothesis testing. From the results of data analysis of the variables studied, namely the teacher competency variable and the learning strategy variable showed that learning from home at SMK Negeri 2 kayuagung was affective, and there was a significant relationship to the learning motivation but there was no significant to the learning outcomes.